Cover Picture: A Glutathione‐Activated Phthalocyanine‐Based Photosensitizer for Photodynamic Therapy (Chem. Eur. J. 21/2014). Issue 21 (14th May 2014) - He, Hui; Lo, Pui‐Chi; Ng, Dennis K. P.
<x xml:space="preserve">Abstract</x> Smart photosensitizers that can be activated selectively by tumor‐associated stimuli are of great potential for targeted photodynamic therapy. They can enhance the overall therapeutic outcome and reduce undesirable side effects. In their Communication on page 6241 ff., H. He, P.‐C. Lo, and D. K. P. Ng report a simple, yet highly efficient, phthalocyanine‐based photosensitizer. Its fluorescence emission and reactive oxygen species generation are greatly enhanced by glutathione, both in phosphate‐buffered saline and inside cancer cells. The activation of this photosensitizer has also been demonstrated in tumor‐bearing nude mice.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>